2011
DOI: 10.1016/j.neuroscience.2011.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Long-term deficiency of circulating and hippocampal insulin-like growth factor I induces depressive behavior in adult mice: a potential model of geriatric depression

Abstract: Numerous studies support the hypothesis that deficiency of insulin-like growth factor I (IGF-1) in adults contributes to depression, but direct evidence is limited. Many psychological and pro-cognitive effects have been attributed to IGF-1, but appropriate animal models of adult-onset IGF-1 deficiency are lacking. In this study, we use a viral-mediated Cre-loxP system to knockout the Igf1 gene in either the liver, neurons of the CA1 region of the hippocampus, or both. Knockout of liver Igf1 reduced serum IGF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 61 publications
2
52
1
Order By: Relevance
“…This is in contrast with studies using animal models or adult patients with GHD (i.e. pathological GHD due to hypothalamic or pituitary defects) that did find supportive evidence for an association between the GH-IGF-1 axis and depression (Duman et al, 2009;Giusti et al, 1998;Kokshoorn et al, 2011;Mahajan et al, 2004;Mitschelen et al, 2011). Possibly, a longitudinal effect of IGF-1 on mood may only be present in a severe IGF-1 deficient state, during which other mechanisms may be involved than during the 'somatopause'.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…This is in contrast with studies using animal models or adult patients with GHD (i.e. pathological GHD due to hypothalamic or pituitary defects) that did find supportive evidence for an association between the GH-IGF-1 axis and depression (Duman et al, 2009;Giusti et al, 1998;Kokshoorn et al, 2011;Mahajan et al, 2004;Mitschelen et al, 2011). Possibly, a longitudinal effect of IGF-1 on mood may only be present in a severe IGF-1 deficient state, during which other mechanisms may be involved than during the 'somatopause'.…”
Section: Discussioncontrasting
confidence: 78%
“…GH supplementation has been shown to improve these symptoms (Kokshoorn et al, 2011;Mahajan et al, 2004). Since features of normal aging resemble those of GHD, it has been suggested that the 'somatopause' contributes to age-associated changes and disorders (Bartke, 2008;Corpas et al, 1993;Mahajan et al, 2004;Mitschelen et al, 2011). For instance, lower IGF-1 concentrations are related to impaired cognitive functioning, which frequently coincides with late-life depression, in healthy elderly (Arwert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both neurons and glial cells express IGF-1, which impacts the developing brain by modulating neural cell signaling and proliferation and by exerting multifunctional actions on the differentiation of progenitor neuronal cells, particularly in the hippocampus of adult rats (Trejo et al, 2001). Deficits in both central and peripheral IGF-1 levels may contribute to the development of affective disorders in humans and lead to the progression of depression-like symptoms in animals (Mitschelen et al, 2011). Furthermore, IGF-1 displays antidepressant-like properties: intracerebroventricular administration of IGF-1 reverses lipopolysaccharide (LPS)-evoked depression-like behavior in rodents (Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%